Associations between birth season and lumbar spine bone mineral density in perimenopausal Polish women - Rosset, Iwona; Spinek, Anna Elżbieta; Stuss, Michał; Sewerynek, Ewa; Żądzińska, Elżbieta (Anthropological Review, 2023)
In European populations, the birth season significantly correlates with many biological features. It is thus possible that the observed clinical effects of bone metabolism disorders are a partial consequence of bone mineral density (BMD), modified by the season of prenatal development (the birth season). The aim of this study was to evaluate the relationship between the birth season and BMD among Polish women in perimenopausal age. A total of 653 Polish women aged 50.0–59.9 years were included in the study. BMDs of lumbar vertebrae were measured by dual-energy x-ray absorptiometry. Statistical analyses were based on measured lumbar BMD values, age, and body mass index (BMI). The analysis of variance (ANOVA) was applied to evaluate the season-related differentiation of mineral density of lumbar vertebrae. BMDs of lumbar vertebrae negatively correlated with age and positively with BMI. We regressed BMD on age and BMI and used the residuals as a measure of age- and BMI-independent lumbar BMD values. The ANOVA results showed that women born in summer had significantly lower BMD of the L1 vertebra compared to those born in autumn, regardless of age and BMI. The results of our study indicate the need to extend the group of risk factors for osteoporosis in Central Europeans with the season of woman’s birth.